2013
DOI: 10.7860/jcdr/2013/5100.3115
|View full text |Cite
|
Sign up to set email alerts
|

Foramen of Civinini: A New Anatomical Guide for Maxillofacial Surgeons

Abstract: Introduction: Study on Morphometric and radiological aspect on existence of foramen of civinini. Sphenoid bone comprises of some rare ossified ligaments, may encounter difficulty in surgical procedures. Incidence of Pterygospinous bars various with different racial groups and they are genetically controlled. Complete ossification of pterygospinous ligament form foramen of civinini. Entrapments of vessels or nerves may occur due to existence of pterygospinous bar. The bar may locate medially or inferiorly to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…According to previous studies, the position of pterygospinous bar was medial or inferior to foramen ovale and the pterygoalar bar was medial, lateral or inferior to the foramen ovale [6,8,14]. In the present study, the pterygospinous bar was most commonly seen to cross the foramen inferiorly and in few cases was medial to the foramen ovale.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…According to previous studies, the position of pterygospinous bar was medial or inferior to foramen ovale and the pterygoalar bar was medial, lateral or inferior to the foramen ovale [6,8,14]. In the present study, the pterygospinous bar was most commonly seen to cross the foramen inferiorly and in few cases was medial to the foramen ovale.…”
Section: Discussionsupporting
confidence: 64%
“…When it is present in varying degrees, it gives rise to ptergoalar and pterygospinous foramen [6,18]. A wide pterygospinous bar exists in skulls of herbivores, rodents, carnivores and mature monkeys and small pterygospinous bar is seen in rodents but not seen in new world monkeys [3,4,6]. Therefore the presence of pterygospinous bar in man is considered to be a phylogenic remnant [4,19].…”
Section: Phylogenymentioning
confidence: 99%
See 2 more Smart Citations
“…Tubbs et al (2009) analyzed 154 adult dry human skulls and reported one pterygospinous foramen (foramen of Civinini) and one pterygoalar foramen (foramen of Hyrtl). A study of 160 skulls revealed complete and incomplete pterygospinous foramina in 1.25% and 7.5%, respectively (Saran et al 2013).…”
Section: Sphenoid Bonementioning
confidence: 99%